KKT transformation approach for multi-objective multi-level linear programming problems - Sinha, Surabhi; Sinha, S.B. (European journal of operational research, 2002)
The earlier Karush–Kuhn–Tucker (KKT) transformation method has been applied to multi-level decentralized programming problems (ML(D)PPs) when the decision variable set was divided into subsets where each decision maker (DM) of the system controlled only a particular subset but had no control over any decision variables of some other subset. In this paper we give the mathematical formulation and corresponding development of ML(D)PPs by KKT transformation when DMs have absolute control over certain decision variables but some variables may be shared and hence controlled by two or more DMs.